Rational actors in balancing markets: a game-theoretic model and results - Thomas Rupp (Technische Universität Darmstadt, Department of Law and Economics, 2006)
Guided by game theory we develop a model to explain behavioral equilibria under uncertainty and interaction with the spot market on balancing markets. We offer some insights for the general model and derive explicit solutions for a specific model in which the error distributions and pricing function are given. The most interesting conclusions are the unique existence of an equilibrium and that no participant acts contrary to the aggregate market (either all market participants buy or sell power) and all strategies are, normalized properly, equal (which is rather counterintuitive). Furthermore the aggregate behavior is a stochastic process varying around its own variance.
Keywords: C73; D58; Q41; D40; 330; game theory; nash equilibrium; regulated energy market; balancing power